The Role of Strategy in Addressing the Dangers of Private Gold Mining – A case study of Abu Hamad area, River Nile State – Sudan – - Elrayah, Ahmed Abdelaziz Ibrahim; Nakchbandi, Ahmad M- Rachid; Bakhiet, Adel Saad jaib allah; Sayed, Musab Sayed Fadoul; Mohamed, Rania Nureldin Osman (Journal of Risk and Crisis Management, 2020)
The paper aims to clarify the role of implementing strategies in developing indigenous mining in Sudan, and methods of treating the damage caused by the extraction of gold by primitive methods. The study dealt with the explanatory factors and theories that helped change. Researchers used the historical, descriptive and analytical method to study the role of strategy implementation, the obstacles and risks facing mining in the study area. The study began by tracing the historical background of the phenomenon of mining and social change, then proceeded to describe the phenomenon understudying all its social, economic, cultural, environmental health and military security dimensions. The analytical approach was also used, as it became clear through the study that there is a great shortage in Arab studies that dealt with the relationship between the mining strategy, optimal mineral resources exploitation, and that primitive gold extraction methods that lead to the waste of large quantities of gold, as well as the lack of revenue collection and tax evasion in addition to smuggling, resulted in government large financial resources loss. As a whole, the study concluded that the competent authorities should arrange the optimal utilization of mineral resources according to a system to expand the national income circles while working to raise awareness as a whole. Several recommendations were made, the most important of which is that residential areas and water sources the area must be moved away from mining markets and areas. Security, safety and health services must also be provided in order to preserve the miners and the people of the mining area.